Concept of frames discarding and multiplexing efficiency - Shah, Asadullah; Dwi Handayani, Dini Oktarina (IIUM Press, 2011)
At low bit rates speech is coded frame by frame, each frame of a size of 20-30ms. Perceptually, each frame may be different, depends upon the speech signal properties (voiced or unvoiced). The frames with lower perception may be one of the potential candidates to be dropped and reconstructed to maximize the bandwidth of the systems. This chapter explains to hO\v these frames might be identified and used for STDM designs.